PENGEMBANGAN MEDIA KOMATIF (KOMIK DIGITAL INTERAKTIF) UNTUK MATERI MEMAKAN DAN DIMAKAN PADA MATA PELAJARAN IPAS KELAS V SD DI GUGUS IX KECAMATAN BULELENG - Kadek Ayu Setia Dewi; I Made Sedana; IG Agung Jaya Suryawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop an interactive digital comic learning media (KOMATIF) on the topic of food chains for fifth-grade elementary students. This research used the ADDIE model consisting of analysis, design, development, implementation, and evaluation stages. Data were collected through observation, interviews, and questionnaires involving experts, teachers, and students. The validation results showed high validity with Aiken’s V scores of 0.92 for material experts, 0.88 for media experts, and 0.89 for language experts. The practicality test conducted in SDN 2 Alasangker and SDN 3 Alasangker showed 99% from teachers and 98% from students, indicating that the media is very practical. The findings reveal that KOMATIF is feasible, easy to use, and able to increase student engagement in learning. Therefore, this media can be used as an innovative learning tool in elementary science education.